Do perforated gastric ulcers require routine intra-operative biopsy? - Oyomno, Meryl Dache (My University, 2018)
Background. It is recommended that perforated peptic ulcers undergo intraoperative biopsy to rule out an occult malignancy. Furthermore, there is a recommendation for routine postoperative outpatient follow-up gastroscopy to examine and biopsy residual ulcers. In view of the low incidence of malignancy (<1%) and the changing epidemiology of perforated gastric ulcers, evidenced by an increased incidence of patients younger than the typical gastric cancer age group (60-79 years), presenting with this condition, the question is raised: is it necessary to biopsy all perforated gastric ulcers at the time of surgical repair? Objectives To determine the demographics and potential risk factors for perforated peptic ulcers as well as the incidence of occult malignancy in these ulcers. Methods A retrospective study was carried out from 1 January 2010 to 31 December 2011 in three public university affiliated hospitals in Johannesburg. Data analysis was conducted using Microsoft ExcelTM spreadsheet tools. The descriptive analysis was carried out as follows. First, categorical variables were summarized by frequency and percentage tabulations and illustrated by means of bar charts. Second, continuous variables were summarized by mean, standard deviation, median, and interquartile range and their distribution illustrated by histograms. The X2 test was used to assess the association between age category, gender, and ulcer location. Fischer’s exact test was used for 2x2 tables and where the requirements for the X2 test could not be met. Finally, the Phi coefficient and Cramer’s V were used to measure the strength of association. Results During the study period 171 patients underwent operative management of perforated ulcers. Most were young (20 – 39 years) with a median age of 42 years, 54.4% of the ulcers were gastric ulcers and intra-operative biopsy was performed in 72% of cases. Of these 25 (26.88 %) were adequate biopsies. Of the inadequate biopsies 97.62% had no mucosa in the biopsy specimen. 90.2% of the biopsies were benign and 2.4% malignant. One case of H. pylori infection was noted. There was a nonattendance rate of 72% for follow-up gastroscopy. For the perforated gastric ulcers, the most prevalent risks factors include smoking (55.9%), NSAIDS (40.0%), and alcohol (34.4%). Conclusion A South African protocol for the management of perforated peptic ulcers, recognizing that most patients do not return for follow-up gastroscopy, should be developed. Intra-operatively biopsy should be performed in view of the low patient follow-up rate, however the biopsy specimen must include mucosa to improve the diagnostic rate of malignancy and H. pylori.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Medicine (General Surgery). Johannesburg, 2018.
Keywords: Gastroscopy; Stomach Ulcer; Peptic Ulcer